Analisis Transmisi Kebijakan Moneter Syariah Terhadap Kinerja UMKM Melalui Sistem Murabahah - Cinta Rahmi; Inki Azir; Vistaufa Wardhatul Chomairha; Azzira Rachmadani (CV. ITTC INDONESIA, 2024)
This article analyzes the concept of sharia monetary policy on the performance of MSMEs, especially during Covid-19 through the murabahah system. The murabahah credit system is an example that can be used by MSME players in starting business activities during the Covid-19 period, through financial institutions that implement sharia monetary policies to avoid usury and getting into debt. Sharia monetary policy is a financial institution that runs based on sharia principles. This research aims to analyze the transmission of sharia monetary policy on the performance of MSMEs during the pandemic. The results of this research were obtained using a descriptive approach. With interview techniques given to MSME actors. Based on the research results, it can be concluded that the transmission of sharia monetary policy on the performance of MSMEs is sufficient to encourage the improvement of actors by providing non-harmful capital access, good money management training, as well as marketing training using information technology.